Frontal sinus meningoencephalocele presenting with spontaneous cerebrospinal fluid leak - Leopold B. Knappe (Otolaryngology Case Reports, 2021)
Spontaneous cerebrospinal fluid (CSF) rhinorrhea is a rare occurrence. It is frequently associated with an encephalocele. A case of a spontaneous meningoencephalocele (MEC) in the frontal sinus is presented, manifesting with unilateral, clear nasal discharge in a 68-year-old female patient. High resolution computed tomography (CT) imaging identified a defect in the posterior table of the left frontal sinus. Magnetic resonance imaging (MRI) confirmed protrusion of meninges and brain tissue through the defect. The endoscopic repair was performed transnasally, after which the patient's symptoms resolved. Classification, etiology, clinical presentation, diagnosis and treatment of sinonasal cephaloceles are discussed.